Recanalization Therapies in Acute Ischemic Stroke: Pharmacological Agents, Devices, and Combinations - Vijay K. Sharma; Hock Luen Teoh; Lily Y. H. Wong; Jie Su; Benjamin K. C. Ong; Bernard P. L. Chan (Stroke Research and Treatment)
The primary aim of thrombolysis in acute ischemic stroke is recanalization of an occluded intracranial artery. Recanalization is an important predictor of stroke outcome as timely restoration of regional cerebral perfusion helps salvage threatened ischemic tissue. At present, intravenously administered tissue plasminogen activator (IV-TPA) remains the only FDA-approved therapeutic agent for the treatment of ischemic stroke within 3 hours of symptom onset. Recent studies have demonstrated safety as well as efficacy of IV-TPA even in an extended therapeutic window. However, the short therapeutic window, low rates of recanalization, and only modest benefits with IV-TPA have prompted a quest for alternative approaches to restore blood flow in an occluded artery in acute ischemic stroke. Although intra-arterial delivery of the thrombolytic agent seems effective, various logistic constraints limit its routine use and as yet no lytic agent have not received full regulatory approval for intra-arterial therapy. Mechanical devices and approaches can achieve higher rates of recanalization but their safety and efficacy still need to be established in larger clinical trials. The field of acute revascularization is rapidly evolving, and various combinations of pharmacologic agents, mechanical devices, and novel microbubble/ultrasound technologies are being tested in multiple clinical trials.